Tradisi Mitoni Pada Masyarakat Katolik - Eka Riani; Nurfitriyana Nurfitriyana; Nugroho Nugroho (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2022)
This thesis is titled “MITONI TRADITION IN CATHOLIC COMMUNITY (Case Study in Harjowinangun Village, Belitang District, Ogan Komering Ulu Timur District)”. The background to this is that many Catholic communities still follow the biennial tradition with Genduren, specifically the biennial rite (mitoni). The Catholic community has abandoned the traditional ritual of bathing seven wells with roses, jasmine and ylang-ylang, changing clothes seven times. The form of the problem is as follows: is the Mitoni tradition in the Catholic community of Harjowinangun village?. What is the role of child prodigies in mitoni worship in Harjowinangun village?. The purpose of the study was to better understand mitoni tradition Catholic community of Harjowinangun and the role of child prodigies in the process of mitoni worship in Harjowinangun village. The result of this study is that the implementation of the mitoni tradition Catholic community in Harjowinangun village starts with the preparation, performing the gendurenan and mitoni cults and takes about an hour. Beginning with the opening rite, introduction to the priest, proclamation of repentance, opening prayer, proclamation of the word, Bible reading, homily, prayer, and after the Our Father, concluding with a prayer willing to end. After the mitoni service is over, the mitoni service participants immediately leave the room. Then everyone enters the dining room to taste the dishes that have been prepared by the host. After the meal, the Catholic community returned to their own homes.